Two genera Foersteria Szépligeti, 1896 and Polydegmon Foerster, 1862 (Hymenoptera, Braconidae, Brachistinae) from China, with description of a new species - Yan, Cheng-Jin; He, Jun-Hua; Chen, Xue-Xin (Zootaxa, 2013)
The genera Foersteria Szépligeti, 1896 and Polydegmon Foerster, 1862 (Hymenoptera, Braconidae, Brachistinae) are re-corded for the first time from China. A new species, Foersteria xinjiangensis Yan & Chen, sp. nov., is described and il-lustrated. A key to the Palaearctic species of Foersteria is given. In addition, Polydegmon sinuatus Foerster, 1862 is illustrated in detail for the first time.